On Tap. (Valdosta State University), no.0 (Spring 2008). - Valdosta State University, Student Life Office (Valdosta State University, 2008)
A student-run, general-interest magazine produced by and for the VSU student community.
Born digital PDF, c.2008. Converted to PDF/A 20170619.
Keywords: Valdosta State University -- Periodicals; College student newspapers and periodicals